2021
DOI: 10.1002/lio2.663
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic disease severity in chronic rhinosinusitis patients and health care utilization

Abstract: Objectives: Chronic rhinosinusitis (CRS) affects approximately 12% of the population and leads to increased health care utilization and indirect costs exceeding $20 billion annually in the United States. The Lund-Mackay score (LMS) measures radiographic disease severity for CRS but poorly correlates with symptom scores. The association between LMS and health care utilization in CRS patients has not yet been investigated. The study aimed to assess the association between health care utilization and CRS radiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Baseline study characteristics of the included studies are summarized in Tables I and II. Briefly, of the 45 included studies, 23 were cross‐sectional studies, 3,6–8,17–35 19 were cohort studies, 10,36–53 two were case–control studies, 54,55 and 1 was a prospective clinical trial 56 . The proportion of males in the included studies ranged from 38% to 84%, while mean age ranged from 33.5 to 58.8 years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Baseline study characteristics of the included studies are summarized in Tables I and II. Briefly, of the 45 included studies, 23 were cross‐sectional studies, 3,6–8,17–35 19 were cohort studies, 10,36–53 two were case–control studies, 54,55 and 1 was a prospective clinical trial 56 . The proportion of males in the included studies ranged from 38% to 84%, while mean age ranged from 33.5 to 58.8 years.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies investigated the CT score in both smokers and non‐smokers with CRS 42,48,53 . While one of the studies demonstrated that the mean LMS was higher in non‐smokers, 48 another found that a higher percentage of non‐smokers had a high LMS compared to smokers (67.3% vs. 32.7%), 53 suggesting that non‐smokers with CRS have more severe sinus opacification. However, in both studies, the p‐value did not reach statistical significance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All patients met the criteria of severe CRS as defined by symptom scores, polyp size, smell impairment, and LMK-CT score. 20,25,26 Changes in outcomes within and between groups We first measured outcome measures from each time-point to baseline within each respective group. We then directly compared outcome effects between dupilumab and FESS by calculating the mean difference in scores between baseline and longitudinal time points.…”
Section: Patient Characteristicsmentioning
confidence: 99%